Dexter is delicious : a novel - Lindsay, Jeffry P. (Doubleday, 2010)
Serial killer Dexter Morgan reevaluates his life views upon the birth of his daughter and investigates the disappearance of a teenage girl who has been running with a group of goths rumored to be engaging in cannibalism.